Structural basis for substrate helix remodeling and cleavage loop activation in the Varkud satellite ribozyme - DasGupta, Saurja (J Am Chem Soc, 2017)
The Varkud satellite (VS) ribozyme catalyzes site-specific RNA cleavage and ligation reactions. Recognition of the substrate involves a kissing loop interaction between the substrate and the catalytic domain of the ribozyme resulting in a rearrangement of the substrate helix register into a so-called ‘shifted’ conformation that is critical for substrate binding and activation. We report a 3.3 Å crystal structure of the complete ribozyme that reveals the active, shifted conformation of the substrate, docked into the catalytic domain of the ribozyme. Comparison to previous NMR structures of isolated, inactive substrates provides a physical description of substrate remodeling, and implicates roles for tertiary interactions in catalytic activation of the cleavage loop. Similarities to the hairpin ribozyme cleavage loop activation suggest general strategies to enhance fidelity in RNA folding and ribozyme cleavage.